Health and socio-demographic background of Ukrainian minors and their families in Germany - challenges for refugee medicine: a cross-sectional study from the German Network University Medicine (NUM) - Hoffmann, Anna Teresa; Kobbe, Robin; Denz, Robin; Maier, Christoph; Toepfner, Nicole; Timmesfeld, Nina; Petersmann, Astrid; Hamprecht, Axel; Skipiol, Katarzyna Emilia (European journal of pediatrics, 2025)
In 2022, over 1,000,000 people from Ukraine fled to Germany, mostly women and children. The aim of this study was to determine health status and socio-demographic background of Ukrainian refugee minors in Germany and to compare that to German minors. In this study, Ukrainian refugees of all ages, who voluntarily made contact with the study centres via flyers or refugee shelters, were interviewed with the help of trained interpreters from 09–12/2022. We assessed data from minors and their families on socio-economic status, general health perception, current and pre-existing infectious and non-contagious diseases, and vaccination status. The data for the minors were collected by interviewing the accompanying adults. In addition, a physical examination and serological screening for infectious and vaccine-preventable diseases were performed. Overall, 392 minors and accompanying adults (358) were included. Minors’ general and mental health were reported as “at least good" in 83% (316) and 80% (304), respectively. In 16% (63), infectious or other underlying diseases were recorded. Tuberculosis infections (7, 1.8%) and hepatitis C (2, 0.5%) were found through the serological tests. HIV could only be detected in one previously known case. Self-reported vaccinations against measles and varicella, for example, did not match serological findings (protection against measles 304; 84%; varicella 230; 64%). Conclusion: Accompanying adults often rate the general health and well-being of Ukrainian refugee minors as rather poor. Frequently, self-reported vaccinations and preexisting diseases did not match serology results; therefore, Ukrainian refugee minors without formal vaccination certificate should be offered all recommended vaccinations and be generously screened for hepatitis B, C and HIV in addition to tuberculosis.
Veröffentlicht: 05. Dezember 2024
Gesehen am 10.06.2025